2004
DOI: 10.1159/000077519
|View full text |Cite
|
Sign up to set email alerts
|

Chromosomal aberrations and risk of cancer in humans: an epidemiologic perspective

Abstract: The pioneering papers published more than one century ago by Theodor Boveri opened the way to extensive research on the mechanism linking chromosomal abnormalities to the pathogenesis of cancer. As a result of this effort, robust theoretical and empirical evidence correlating cytogenetic damage to early stages of cancer in humans was consolidated, and an increased cancer risk was postulated in healthy subjects with high levels of chromosomal aberrations (CA). The first epidemiological investigation aimed at va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
105
0
3

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 188 publications
(112 citation statements)
references
References 22 publications
4
105
0
3
Order By: Relevance
“…Consistent with our findings, M'Kacher et al [2003] analyzing eight patients treated with MOPP/ ABV found no correlation between the frequency of GCR and the patient's age, time after treatment, disease stage, or chemotherapy dose, indicating that there are clear individual variability in the response to anticancer treatment [M'Kacher et al, 2003]. Individual variance is most likely caused by differences in DNA-metabolizing enzymes or DNA repair capabilities [M'Kacher et al, 2003;Bonassi et al, 2004;Hagmar et al, 2004;Allan and Travis, 2005].…”
Section: Complex Structural Chromosome Damage Is Increased In Hl Survsupporting
confidence: 88%
“…Consistent with our findings, M'Kacher et al [2003] analyzing eight patients treated with MOPP/ ABV found no correlation between the frequency of GCR and the patient's age, time after treatment, disease stage, or chemotherapy dose, indicating that there are clear individual variability in the response to anticancer treatment [M'Kacher et al, 2003]. Individual variance is most likely caused by differences in DNA-metabolizing enzymes or DNA repair capabilities [M'Kacher et al, 2003;Bonassi et al, 2004;Hagmar et al, 2004;Allan and Travis, 2005].…”
Section: Complex Structural Chromosome Damage Is Increased In Hl Survsupporting
confidence: 88%
“…Importantly for the validation of cytogenetic biomarkers as early parameters for cancer prediction, the causal relationship between chromosomal aberrations and cancer risk has been described in cohort studies 59 .…”
Section: Application Of Biomarkers To Environmental Risk Assessmentmentioning
confidence: 99%
“…In this scenario, the additional information obtained with cytogenetic studies, complement physical dosimetry data and enables better evaluation of the radiation health effects. It is known that cancer incidence among healthy individuals of a population increases with increased levels of CAs in their circulating lymphocytes (Bonassi et al, 2000(Bonassi et al, , 2004. Because an increased frequency of CAs was found to be a sensitive indicator of exposure to IR (Carrano and Natarajan, 1988), the CAs assay has been applied to monitor workers professionally exposed to low but cumulative levels of IR (Lazutka et al, 1999;Zakeri and Hirobe, 2010;Bonassi et al, 1997;Maffei et al, 2004;Ballardin et al, 2007).…”
Section: Introductionmentioning
confidence: 99%